Eu@MOF fluorescent test paper for rapid detection of phosphate in environmental water body in situ
Patent Information
- Application Number
- CN202611270982.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]为了解决现有技术中荧光检测试纸抗pH干扰能力有限、耐浸泡稳定性不足,难以适配无预处理天然水体原位检测的问题,本申请提供用于环境水体磷酸根原位快速检测的Eu@MOF荧光试纸
[0033]1、由于本申请采用聚多巴胺改性玻璃纤维素支撑基底,搭配氨基丙基磺酸甜菜碱与聚多巴胺共沉积的固载化两性离子缓冲界面层,由于缓冲层可在传感界面维持稳定的局部反应微环境,各功能层间通过共价作用形成稳定结合,获得了良好的宽pH水体适配性与结构耐浸泡性,可适配原位无预处理的天然水体检测场景。
Smart Images

Figure CN123008741A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of environmental water quality testing and functional sensing materials technology, and more specifically, it relates to Eu@MOF fluorescent test paper for in-situ rapid detection of phosphate in environmental water bodies. Background Technology
[0002] Phosphate content in aquatic environments is one of the core indicators for evaluating the degree of eutrophication. Rapid and accurate detection of phosphate concentration in water is of great significance for water quality monitoring and ecological assessment. Fluorescent sensor strips have the advantages of being easy to operate, having a fast response, and requiring no large-scale detection equipment, making them a commonly used technique in on-site water quality testing. Among them, fluorescent strips based on rare earth metal-organic framework materials have been widely studied and applied due to their strong specific recognition capabilities.
[0003] Currently, most conventional rare earth MOF fluorescent test strips require the use of a liquid buffer system. Before testing, water samples need to undergo pretreatment operations such as pH adjustment. In the scenario of in-situ immersion testing in natural water bodies, the pH value of the water body fluctuates within a certain range. The test strip itself lacks the ability to regulate the interface microenvironment, and the detection signal is easily affected by pH changes, resulting in deviations. At the same time, the bonding stability between the functional coating and the substrate is limited, and components are easily lost under long-term immersion, making it difficult to adapt to the in-situ detection requirements without pretreatment. Summary of the Invention
[0004] To address the limitations of existing fluorescent test strips in terms of pH interference resistance and immersion stability, making them unsuitable for in-situ detection in untreated natural water bodies, this application provides Eu@MOF fluorescent test strips for rapid in-situ detection of phosphate in environmental water bodies.
[0005] Firstly, this application provides Eu@MOF fluorescent test strips for in-situ rapid detection of phosphate in environmental water bodies, employing the following technical solution:
[0006] The Eu@MOF fluorescent test paper for in-situ rapid detection of phosphate in environmental water comprises, from bottom to top, a polydopamine-modified glass cellulose support substrate, a supported zwitterionic buffer interface layer, and a functional sensing layer. The supported zwitterionic buffer interface layer is covalently grafted onto the modified surface of the polydopamine-modified glass cellulose support substrate, and the functional sensing layer is cross-linked and immobilized on the surface of the supported zwitterionic buffer interface layer. Based on dry weight, the functional sensing layer comprises the following components: 1.2–1.8 parts of dual-ligand co-coordinated Eu@MOF powder, 0.06–0.10 parts of branched polyethyleneimine, 0.01–0.02 parts of quaternized polyethyleneimine, and 0.06–0.10 parts of polyethylene glycol.
[0007] By adopting the above technical solution, polydopamine modification can introduce a large number of phenolic hydroxyl and quinone active sites on the surface of chemically inert glass cellulose, providing a reliable interface basis for the stable binding of the upper functional structure. The immobilized zwitterionic buffer interface layer can maintain a relatively stable local reaction microenvironment at the sensing interface, weakening the interference of water pH fluctuations on the detection system. The polymer components in the functional sensing layer work synergistically to construct a polymer network that has both ion mass transfer and structural immobilization functions. Among them, the cationic modified components can enrich the target analytes through electrostatic interaction, the network framework can fix fluorescent functional powders, and the layers form a stable overall structure through covalent interaction, enabling the test strip to be adapted to in-situ detection scenarios in natural water bodies without pretreatment.
[0008] Preferably, the dual-ligand co-coordinated Eu@MOF powder is a single-framework co-coordinated crystal phase, prepared by a solvothermal reaction of europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate, with a molar ratio of 1:(0.8-1.2):(0.15-0.3):(2.0-3.0).
[0009] By adopting the above technical solution, two organic ligands with different structures participate in coordination within the same MOF framework. The structural advantages of different ligands can be combined to regulate the fluorescence performance and recognition ability of the material. The single-framework crystalline phase structure can avoid the two ligands from nucleating separately to form a mixed crystal system, ensuring the batch stability and uniformity of the fluorescence signal, making the signal output of ratiometric fluorescence detection more reliable, and improving the accuracy of semi-quantitative detection.
[0010] Preferably, the immobilized zwitterionic buffer interface layer is a composite thin layer formed by co-deposition of aminopropyl sulfonate betaine and polydopamine, with a thickness of 10-20 μm.
[0011] By adopting the above technical solution, a zwitterionic buffer and polydopamine are simultaneously deposited to form a composite structure. This allows some of the buffer to be covalently bonded to the polydopamine network, while some of the buffer is embedded inside the three-dimensional network. This not only improves the immobilization strength of the buffer component but also increases the number of buffer groups per unit area. This thickness range can control the mass transfer resistance while ensuring the buffer capacity, and avoid the excessively thick interface layer from extending the ion diffusion path and affecting the detection response speed.
[0012] Preferably, the thickness of the polydopamine-modified glass cellulose support substrate is 0.2 to 0.3 mm.
[0013] By adopting the above technical solution, the glass cellulose substrate in this thickness range has both good mechanical support performance and pore transport performance. It can provide a stable bearing base for multi-layer functional coatings, avoid bending and damage during the use of test strips, and rely on its own pore structure to assist water transport, ensuring the efficiency of liquid phase mass transfer during the detection process, thus taking into account both the operability and detection response performance of the test strips.
[0014] Secondly, this application provides a method for preparing Eu@MOF fluorescent test strips for in-situ rapid detection of phosphate in environmental water bodies, using the following technical solution:
[0015] The preparation method of Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies includes the following steps:
[0016] S1. Powder preparation: Weigh europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate according to the preset molar ratio, add them to the mixed solvent and ultrasonically disperse them, transfer them to a hydrothermal reactor for solvothermal reaction, and after natural cooling, centrifuge, wash and vacuum dry them in sequence to obtain dual-ligand co-coordinated Eu@MOF powder;
[0017] S2. Substrate modification: The glass cellulose membrane substrate is immersed in anhydrous ethanol and ultrasonically cleaned. After being taken out and dried, it is immersed in polydopamine modification solution and reacted at room temperature in the dark. After being taken out, it is rinsed with deionized water until the washing solution is colorless. After drying, polydopamine modified glass cellulose support substrate is obtained.
[0018] S3. Buffer layer construction: The polydopamine-modified glass cellulose support substrate was immersed in the amphoteric buffer reaction solution and co-deposition grafting reaction was carried out at room temperature in the dark. After removal, the substrate was rinsed with deionized water to remove free components and dried to form an immobilized zwitterionic buffer interface layer on the modified surface of the substrate.
[0019] S4. Preparation of coating solution: Disperse the dual-ligand co-coordinated Eu@MOF powder in deionized water and ultrasonically disperse to form a uniform suspension. Add branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent to the suspension in sequence, and continue ultrasonic dispersion to obtain the functional composite sensing coating solution.
[0020] S5. Curing and molding: The functional composite sensing coating liquid is uniformly coated onto the substrate surface with the immobilized zwitterionic buffer interface layer using a scraping method. After controlling the wet film thickness, it is placed in a constant temperature environment for curing. After cutting, Eu@MOF fluorescent test paper is obtained.
[0021] By adopting the above technical solution and using a step-by-step, layer-by-layer preparation process, the preparation of fluorescent functional powder, substrate interface modification, construction of buffer functional layer, preparation and curing of sensing coating liquid are completed sequentially. The product of each step can provide a matching structural basis for subsequent steps. The operating conditions of each step are mild and controllable. Without the need for complex special equipment, fluorescent test strips with clear layer structure, strong adhesion and uniform performance can be stably prepared with small performance differences between batches.
[0022] Preferably, in step S1, the mixed solvent is composed of N,N-dimethylformamide, anhydrous ethanol and deionized water in a volume ratio of 6:(1.8-2.2):(1.8-2.2), the temperature of the solvothermal reaction is 115-125℃, and the reaction time is 7-9h. After centrifugation, the reaction product is subjected to solvent exchange with anhydrous ethanol 2-3 times, isothermal coordination repair treatment at 60-80℃ for 12-16h, and then vacuum drying.
[0023] By adopting the above technical solution, the mixed solvent of this ratio can control the nucleation rate and growth morphology of MOF crystals by adjusting the polarity and water activity of the system, ensuring the formation of a uniform single-framework crystal phase. The solvent exchange process can replace the high-boiling-point solvent and unreacted small molecule raw materials remaining in the crystal channels. The isothermal coordination repair treatment can promote the re-binding of free ligands on the crystal surface with the coordination unsaturated metal sites in a mild liquid environment, reduce the active defects on the crystal surface, and improve the structural stability of the phosphor in the aqueous environment.
[0024] Preferably, in step S2, the polydopamine modification solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0 to 9.0, the solute in the polydopamine modification solution is dopamine hydrochloride, and the solute concentration is 1.5 to 2.5 mg / mL; the drying temperature is 55 to 65°C, and the drying method is vacuum drying.
[0025] By adopting the above technical solution, the buffer system with this pH range can be adapted to the self-polymerization reaction conditions of dopamine, so that the dopamine monomer slowly oxidizes and deposits on the substrate surface to form a uniform modified layer. The concentration range of dopamine hydrochloride can control the thickness of the modified layer and the density of surface active sites. With the corresponding reaction time, a modified substrate with moderate binding strength and sufficient activity can be obtained. Vacuum drying conditions can gently remove the residual solvent and moisture in the substrate and avoid structural damage to the modified layer.
[0026] Preferably, in step S3, the amphoteric buffer reaction solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 7.5–8.5, and the solutes are aminopropyl sulfonate betaine and dopamine hydrochloride; wherein the concentration of aminopropyl sulfonate betaine is 4–6 mg / mL and the concentration of dopamine hydrochloride is 0.5–1.0 mg / mL; the drying temperature is 40–50°C, and the drying method is vacuum drying.
[0027] By adopting the above technical solution, the two solutes in the reaction solution can react simultaneously under the pH conditions. While dopamine hydrochloride is gradually oxidized and polymerized, it can combine with the terminal amino group of aminopropyl sulfonate betaine through Michael addition reaction. The two are deposited together on the substrate surface to form a composite buffer layer. The concentration ratio of the two components can control the content of buffer groups and the density of the network structure in the composite layer. With the corresponding reaction time, a uniform thickness and stable buffering performance interface layer can be obtained. Vacuum drying treatment can slowly solidify the composite layer and avoid the cracking and peeling problems caused by rapid drying.
[0028] Preferably, in step S4, the final concentration of the dual-ligand co-coordinated Eu@MOF powder in the suspension is 1.2–1.8 mg / mL, the final concentration of the branched polyethyleneimine is 0.06–0.10 mg / mL, the amount of quaternized polyethyleneimine added is 10–15% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine, the amount of polyethylene glycol added is 5–8% of the total mass of the coating solution, and the crosslinking agent is ethylene glycol diglycidyl ether, the amount added is 2–5% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine.
[0029] By adopting the above technical solutions, the phosphor powder in this concentration range can ensure sufficient recognition sites in the sensing layer. Branched polyethyleneimine, as the basic framework of the polymer network, can provide a large number of reaction sites. Quaternized ammonium modified polyethyleneimine can introduce positively charged sites and actively enrich phosphate anions in water through electrostatic interaction. Polyethylene glycol can adjust the hydrophilicity of the sensing layer and promote the diffusion and transport of ions in the membrane layer. The crosslinking agent can undergo ring-opening reaction with the amino groups on the polymer chain to form a three-dimensional covalent network to embed and fix the phosphor powder. With the corresponding dispersion process, a uniform and stable coating system can be obtained, ensuring the uniformity of the performance of the cured membrane layer.
[0030] Preferably, in step S5, the wet film thickness is 55–65 μm, the curing temperature is 40–50 °C, and the curing time is 2–3 h.
[0031] By adopting the above technical solution, the wet film thickness within this range can be adjusted to control the load and structural uniformity of the final sensing layer, avoiding weak detection signals caused by excessively thin coatings or slow mass transfer and easy peeling caused by excessively thick coatings. The mild curing conditions within this temperature range allow the crosslinking reaction to proceed smoothly, while allowing the solvent to evaporate slowly and evenly, avoiding film cracking, curling, and peeling caused by high-temperature rapid drying. The corresponding curing time can ensure that the crosslinking reaction is fully completed, forming a structurally stable polymer network and improving the water immersion resistance of the sensing layer.
[0032] In summary, this application has the following beneficial effects:
[0033] 1. Because this application uses a polydopamine-modified glass cellulose support substrate, combined with an immobilized zwitterionic buffer interface layer co-deposited with aminopropyl sulfonate betaine and polydopamine, the buffer layer can maintain a stable local reaction microenvironment at the sensing interface. The functional layers form a stable bond through covalent interaction, thus achieving good wide pH water body adaptability and structural immersion resistance, which can be adapted to in-situ untreated natural water body detection scenarios.
[0034] 2. In this application, quaternized polyethyleneimine combined with ethylene glycol diglycidyl ether is preferred to construct the polymer network of the sensing layer. Since the quaternized component can actively enrich phosphate anions through electrostatic interaction, and the crosslinking agent can form a three-dimensional covalent network to embed and fix MOF powder, better detection response speed, detection sensitivity and long-term stability are obtained.
[0035] 3. The method of this application, by adding anhydrous ethanol solvent exchange and isothermal coordination repair treatment after the solvothermal synthesis process, allows the free ligands on the crystal surface to re-bind with the coordination unsaturated metal sites, reducing the surface hydrolysis active sites, thus obtaining better aqueous stability of MOF powder and reducing the fluorescence baseline drift amplitude under long-term water immersion.
[0036] 4. In this application, dual-ligand Eu@MOF powder with a single-framework co-coordinated crystal phase is further used as the fluorescence sensing unit. Since two functional ligands are introduced into the single crystal phase system at the same time, the phase separation inhomogeneity problem of the dual-material blend system can be avoided, and a more stable ratio fluorescence signal is obtained, which can improve the signal reliability and accuracy of semi-quantitative detection. Attached Figure Description
[0037] Figure 1 This is a flowchart of the preparation method of Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies provided in this application;
[0038] Figure 2 This is a comparison chart of the phosphate fluorescence detection performance test results of the various embodiments and comparative examples provided in this application;
[0039] Figure 3 This is a comparison chart of the anti-interference performance test results of various embodiments and comparative examples in wide pH water bodies provided in this application;
[0040] Figure 4 This is a comparison chart showing the performance retention rate test results of the various embodiments and comparative examples provided in this application after continuous immersion in water for 72 hours. Detailed Implementation
[0041] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.
[0042] Technical Concept: Existing fluorescent test strips based on rare-earth MOFs are mostly suitable for testing pretreated laboratory water samples, but their applicability in real-world scenarios involving in-situ immersion testing in natural water bodies is insufficient. The main reason for this problem is that existing test strips lack a solid-phase interface microenvironment regulation structure. The fluorescence recognition process is easily interfered with by direct fluctuations in the pH of the water body, requiring the addition of liquid-phase buffer reagents or pH adjustment of the water sample to ensure detection accuracy. At the same time, the functional coating and the substrate are mostly physically bonded, with limited bonding strength. Active components are prone to loss under long-term immersion in water. The insufficient aqueous stability of the MOF material itself also exacerbates signal attenuation, making it difficult to meet the requirements for long-term in-situ detection.
[0043] This scheme adopts a layer-by-layer functionalized structural design. First, an active reaction interface is constructed on the surface of a glass cellulose substrate through polydopamine modification, providing stable covalent binding sites for the upper functional structure. Then, a buffer interface layer composed of aminopropyl sulfonate betaine and polydopamine is constructed through a co-deposition grafting process. The local reaction environment of the sensing area is maintained by the immobilized zwitterionic groups, which weakens the influence of water pH fluctuations on the detection signal. At the same time, a polymer network with synergistic cation enrichment and covalent cross-linking is constructed in the sensing layer. Combined with the isothermal coordination repair post-treatment of MOF powder, the overall structure's water immersion stability and detection response performance are improved, making the test strip suitable for in-situ detection in natural water bodies without pretreatment.
[0044] Preparation Example 1: The preparation method of quaternized polyethyleneimine is as follows: Weigh 10.0 parts by mass of branched polyethyleneimine and add it to a reaction vessel. Add 80.0 parts by mass of deionized water and stir until completely dissolved. Heat the system to 50°C and maintain a constant temperature. Slowly add 12.5 parts by mass of 2,3-epoxypropyltrimethylammonium chloride over a period of 2 hours. After the addition is complete, continue to stir and maintain the temperature for 6 hours. After the reaction is complete, transfer the reaction solution into a dialysis bag with a molecular weight cutoff of 1000 and dialyze it in deionized water for 72 hours to remove unreacted substances. Small molecule raw materials and salt impurities were dialyzed, and the solution was transferred to a freeze dryer and dried for 48 hours to obtain quaternized polyethyleneimine solid. The degree of quaternization of the product was tested by potentiometric acid-base titration, and the residual amino content was calculated by titrating with 0.1 mol / L hydrochloric acid standard solution using phenolphthalein as an indicator. The degree of quaternization of the product was 42.3%. The number average molecular weight of the product was tested by gel permeation chromatography, and the calculation was performed using narrow-distribution polyethylene glycol as a standard. The number average molecular weight of the product was 3600.
[0045] Preparation Example 2: The preparation method of aminopropyl sulfonate betaine is as follows: Weigh 10.2 parts by mass of N,N-dimethyl-1,3-propanediamine and add it to a reaction vessel. Add 60.0 parts by mass of anhydrous ethanol and stir evenly. Place the system in an ice bath to cool to 0°C. Under nitrogen protection, slowly add 12.2 parts by mass of 1,3-propanesulfonyl lactone over a period of 3 hours. After the addition is complete, heat the system to 40°C and continue to stir and seal for 12 hours. After the reaction is complete, allow the system to cool naturally to room temperature. Collect the precipitated crude product by filtration. The crude product was recrystallized twice with anhydrous ethanol and dried in a vacuum drying oven at 40℃ for 12 h to obtain aminopropyl sulfonic acid betaine. The purity of the product was determined by high performance liquid chromatography (HPLC) and calculated quantitatively using the external standard method. The purity of the product was 99.2%. The molecular structure of the product was characterized and verified by 400MHz proton nuclear magnetic resonance (HMR) spectroscopy. The characteristic peaks of the HMR spectrum completely matched the target molecular structure. The zwitterionic equivalent of the product was determined by acid-base back titration and was 3.28 mmol / g.
[0046] Example 1: This example provides an Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water. From bottom to top, it comprises a polydopamine-modified glass cellulose support substrate, a supported zwitterionic buffer interface layer, and a functional sensing layer. The supported zwitterionic buffer interface layer is covalently grafted onto the modified surface of the polydopamine-modified glass cellulose support substrate, and the functional sensing layer is cross-linked and immobilized on the surface of the supported zwitterionic buffer interface layer. By dry basis mass, the functional sensing layer consists of the following components: 1.5 parts of dual-ligand co-coordinated Eu@MOF powder, 0.08 parts of branched polyethyleneimine, 0.015 parts of quaternized polyethyleneimine, and 0.08 parts of polyethylene glycol.
[0047] Among them, the dual-ligand co-coordinated Eu@MOF powder is a single-framework co-coordinated crystalline phase, prepared by solvothermal reaction of europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate, with a molar ratio of 1:1.0:0.225:2.5; the supported zwitterionic buffer interface layer is a composite thin layer formed by co-deposition of aminopropyl sulfonate betaine and polydopamine, with a thickness of 15 μm. The aminopropyl sulfonate betaine is the product obtained in Preparation Example 2, with a purity of 99.2%; the polydopamine-modified glass cellulose support substrate has a thickness of 0.25 mm, the quaternized polyethyleneimine is the product obtained in Preparation Example 1, with a number average molecular weight of 3600 and a degree of quaternization of 42.3%, and the polyethylene glycol has a molecular weight of 6000.
[0048] The preparation method of the above-mentioned Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water includes the following steps:
[0049] S1. Powder preparation: Weigh europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate according to the preset molar ratio, add them to the mixed solvent and ultrasonically disperse them, transfer them to a hydrothermal reactor for solvothermal reaction, and after natural cooling, centrifuge, wash and vacuum dry them in sequence to obtain dual-ligand co-coordinated Eu@MOF powder.
[0050] The mixed solvent was composed of N,N-dimethylformamide, anhydrous ethanol, and deionized water in a volume ratio of 6:2:2. The ultrasonic dispersion power was 300W, and the dispersion time was 10 min. The solvothermal reaction temperature was 120℃, and the reaction time was 8 h. After centrifugation, the reaction product was subjected to solvent exchange twice with anhydrous ethanol, and then subjected to isothermal coordination repair treatment at 70℃ for 14 h, followed by vacuum drying at 60℃ for 12 h. This isothermal coordination repair treatment can repair unsaturated coordination sites on the crystal surface and improve the aqueous phase stability of the powder.
[0051] S2. Substrate modification: The glass cellulose membrane substrate is immersed in anhydrous ethanol and ultrasonically cleaned. After being taken out and dried, it is immersed in polydopamine modification solution and reacted at room temperature in the dark. After being taken out, it is rinsed with deionized water until the washing solution is colorless. After drying, polydopamine modified glass cellulose support substrate is obtained.
[0052] The polydopamine modification solution was a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5. The solute in the polydopamine modification solution was dopamine hydrochloride with a solute concentration of 2.0 mg / mL. The ultrasonic cleaning power was 200 W and the cleaning time was 5 min. The reaction time at room temperature in the dark was 14 h. The drying temperature was 60 °C and the drying method was vacuum drying for 8 h.
[0053] S3. Buffer layer construction: The polydopamine-modified glass cellulose support substrate is immersed in the amphoteric buffer reaction solution and co-deposition grafting reaction is carried out at room temperature in the dark. After removal, the substrate is rinsed with deionized water to remove free components and dried to form an immobilized zwitterionic buffer interface layer on the modified surface of the substrate.
[0054] The amphoteric buffer reaction solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0, and the solutes are aminopropyl sulfonate betaine and dopamine hydrochloride. The concentration of aminopropyl sulfonate betaine is 5 mg / mL, and the concentration of dopamine hydrochloride is 0.75 mg / mL. The co-deposition grafting reaction time is 6 h. The drying temperature is 45 °C, the drying method is vacuum drying, and the drying time is 10 h. This composite buffer layer can stabilize the local reaction environment in water bodies with wide pH fluctuations, ensuring the stability of the detection signal.
[0055] S4. Preparation of coating solution: Disperse the dual-ligand co-coordinated Eu@MOF powder in deionized water and ultrasonically disperse to form a uniform suspension. Add branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent to the suspension in sequence, and continue ultrasonic dispersion to obtain the functional composite sensing coating solution.
[0056] The final concentration of the dual-ligand co-coordinated Eu@MOF powder in the suspension was 1.5 mg / mL, the final concentration of branched polyethyleneimine was 0.08 mg / mL, and the amount of quaternized polyethyleneimine added accounted for 12.5% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the amount of polyethylene glycol added accounted for 6.5% of the total mass of the coating solution; the crosslinking agent was ethylene glycol diglycidyl ether, and the amount added accounted for 3.5% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the initial ultrasonic dispersion power was 250 W and the duration was 15 min, and the ultrasonic dispersion time continued for 10 min after the material was added. During the dispersion process, magnetic stirring at 300 r / min was used to ensure the uniformity of the system.
[0057] S5. Curing and molding: The functional composite sensing coating liquid is uniformly coated onto the substrate surface with the immobilized zwitterionic buffer interface layer using a scraping method. After controlling the wet film thickness, it is placed in a constant temperature environment for curing. After cutting, Eu@MOF fluorescent test paper is obtained.
[0058] The wet film thickness was 60 μm, the curing temperature was 45℃, and the curing time was 2.5 h; the size of the cut test strip was 0.5 cm × 3.0 cm.
[0059] Example 2: This example provides an Eu@MOF fluorescent test paper for in-situ rapid detection of phosphate in environmental water. From bottom to top, it comprises a polydopamine-modified glass cellulose support substrate, a supported zwitterionic buffer interface layer, and a functional sensing layer. The supported zwitterionic buffer interface layer is covalently grafted onto the modified surface of the polydopamine-modified glass cellulose support substrate, and the functional sensing layer is cross-linked and immobilized on the surface of the supported zwitterionic buffer interface layer. By dry basis mass, the functional sensing layer consists of the following components: 1.2 parts of dual-ligand co-coordinated Eu@MOF powder, 0.06 parts of branched polyethyleneimine, 0.01 parts of quaternized polyethyleneimine, and 0.06 parts of polyethylene glycol.
[0060] Among them, the dual-ligand co-coordinated Eu@MOF powder is a single-framework co-coordinated crystal phase, which is prepared by solvothermal reaction of europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate, with a molar ratio of 1:0.8:0.15:2.0; the supported zwitterionic buffer interface layer is a composite thin layer formed by co-deposition of aminopropyl sulfonate betaine and polydopamine, with a thickness of 10 μm. The aminopropyl sulfonate betaine is the product obtained in Preparation Example 2 with a purity of 99.2%; the substrate thickness of the polydopamine modified glass cellulose support substrate is 0.2 mm, and the quaternized polyethyleneimine is prepared by adjusting the parameters of the synthesis process in Preparation Example 1. The molecular weight of the polyethylene glycol is 2000.
[0061] The preparation method of the above-mentioned Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water includes the following steps:
[0062] S1. Powder preparation: Weigh europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate according to the preset molar ratio, add them to the mixed solvent and ultrasonically disperse them, transfer them to a hydrothermal reactor for solvothermal reaction, and after natural cooling, centrifuge, wash and vacuum dry them in sequence to obtain dual-ligand co-coordinated Eu@MOF powder.
[0063] The mixed solvent was composed of N,N-dimethylformamide, anhydrous ethanol, and deionized water in a volume ratio of 6:1.8:1.8. The ultrasonic dispersion power was 280W, and the dispersion time was 8 minutes. The solvothermal reaction temperature was 115℃, and the reaction time was 7 hours. After centrifugation, the reaction product was subjected to solvent exchange twice with anhydrous ethanol, and then subjected to isothermal coordination repair treatment at 60℃ for 12 hours. Finally, it was vacuum dried at 55℃ for 10 hours. This isothermal coordination repair treatment can repair the unsaturated coordination sites on the crystal surface and improve the aqueous phase stability of the powder.
[0064] S2. Substrate modification: The glass cellulose membrane substrate is immersed in anhydrous ethanol and ultrasonically cleaned. After being taken out and dried, it is immersed in polydopamine modification solution and reacted at room temperature in the dark. After being taken out, it is rinsed with deionized water until the washing solution is colorless. After drying, polydopamine modified glass cellulose support substrate is obtained.
[0065] The polydopamine modification solution was a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0. The solute in the polydopamine modification solution was dopamine hydrochloride with a solute concentration of 1.5 mg / mL. The ultrasonic cleaning power was 180 W and the cleaning time was 4 min. The reaction time at room temperature in the dark was 12 h. The drying temperature was 55 °C and the drying method was vacuum drying for 7 h.
[0066] S3. Buffer layer construction: The polydopamine-modified glass cellulose support substrate is immersed in the amphoteric buffer reaction solution and co-deposition grafting reaction is carried out at room temperature in the dark. After removal, the substrate is rinsed with deionized water to remove free components and dried to form an immobilized zwitterionic buffer interface layer on the modified surface of the substrate.
[0067] The amphoteric buffer reaction solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 7.5, and the solutes are aminopropyl sulfonate betaine and dopamine hydrochloride. The concentration of aminopropyl sulfonate betaine is 4 mg / mL, and the concentration of dopamine hydrochloride is 0.5 mg / mL. The co-deposition grafting reaction time is 5 h. The drying temperature is 40 °C, the drying method is vacuum drying, and the drying time is 8 h. This composite buffer layer can stabilize the local reaction environment within the pH range of conventional surface water, ensuring the stability of the detection signal.
[0068] S4. Preparation of coating solution: Disperse the dual-ligand co-coordinated Eu@MOF powder in deionized water and ultrasonically disperse to form a uniform suspension. Add branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent to the suspension in sequence, and continue ultrasonic dispersion to obtain the functional composite sensing coating solution.
[0069] The final concentration of the dual-ligand co-coordinated Eu@MOF powder in the suspension was 1.2 mg / mL, the final concentration of branched polyethyleneimine was 0.06 mg / mL, and the amount of quaternized polyethyleneimine added accounted for 10% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the amount of polyethylene glycol added was 5% of the total mass of the coating solution; the crosslinking agent was ethylene glycol diglycidyl ether, and the amount added accounted for 2% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the initial ultrasonic dispersion power was 220 W and the duration was 12 min, and the ultrasonic dispersion time continued for 8 min after feeding. During the dispersion process, magnetic stirring at 250 r / min was used to ensure the uniformity of the system.
[0070] S5. Curing and molding: The functional composite sensing coating liquid is uniformly coated onto the substrate surface with the immobilized zwitterionic buffer interface layer using a scraping method. After controlling the wet film thickness, it is placed in a constant temperature environment for curing. After cutting, Eu@MOF fluorescent test paper is obtained.
[0071] The wet film thickness was 55 μm, the curing temperature was 40℃, and the curing time was 2 h; the size of the cut test strip was 0.4 cm × 2.8 cm.
[0072] Example 3: This example provides an Eu@MOF fluorescent test paper for in-situ rapid detection of phosphate in environmental water. From bottom to top, it includes a polydopamine-modified glass cellulose support substrate, a supported zwitterionic buffer interface layer, and a functional sensing layer. The supported zwitterionic buffer interface layer is covalently grafted onto the modified surface of the polydopamine-modified glass cellulose support substrate, and the functional sensing layer is cross-linked and immobilized on the surface of the supported zwitterionic buffer interface layer. By dry basis, the functional sensing layer is composed of the following components: 1.8 parts of dual-ligand co-coordinated Eu@MOF powder, 0.10 parts of branched polyethyleneimine, 0.02 parts of quaternized polyethyleneimine, and 0.10 parts of polyethylene glycol.
[0073] Among them, the dual-ligand co-coordinated Eu@MOF powder is a single-framework co-coordinated crystal phase, which is prepared by solvothermal reaction of europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate, with a molar ratio of 1:1.2:0.3:3.0; the supported zwitterionic buffer interface layer is a composite thin layer formed by co-deposition of aminopropyl sulfonate betaine and polydopamine, with a thickness of 20 μm. The aminopropyl sulfonate betaine is the product obtained in Preparation Example 2 with a purity of 99.2%; the substrate thickness of the polydopamine modified glass cellulose support substrate is 0.3 mm, and the quaternized polyethyleneimine is prepared by adjusting the parameters of the synthesis process in Preparation Example 1. The molecular weight of the polyethylene glycol is 10000.
[0074] The preparation method of the above-mentioned Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water includes the following steps:
[0075] S1. Powder preparation: Weigh europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate according to the preset molar ratio, add them to the mixed solvent and ultrasonically disperse them, transfer them to a hydrothermal reactor for solvothermal reaction, and after natural cooling, centrifuge, wash and vacuum dry them in sequence to obtain dual-ligand co-coordinated Eu@MOF powder.
[0076] The mixed solvent was composed of N,N-dimethylformamide, anhydrous ethanol, and deionized water in a volume ratio of 6:2.2:2.2. The ultrasonic dispersion power was 320W, and the dispersion time was 12 min. The solvothermal reaction temperature was 125℃, and the reaction time was 9 h. After centrifugation, the reaction product was subjected to solvent exchange with anhydrous ethanol three times, and then subjected to isothermal coordination repair treatment at 80℃ for 16 h, followed by vacuum drying at 65℃ for 14 h. This isothermal coordination repair treatment can repair unsaturated sites on the crystal surface and improve the aqueous phase stability of the powder.
[0077] S2. Substrate modification: The glass cellulose membrane substrate is immersed in anhydrous ethanol and ultrasonically cleaned. After being taken out and dried, it is immersed in polydopamine modification solution and reacted at room temperature in the dark. After being taken out, it is rinsed with deionized water until the washing solution is colorless. After drying, polydopamine modified glass cellulose support substrate is obtained.
[0078] The polydopamine modification solution was a tris(hydroxymethyl)aminomethane buffer solution with a pH of 9.0, and the solute in the polydopamine modification solution was dopamine hydrochloride with a solute concentration of 2.5 mg / mL. The ultrasonic cleaning power was 220 W, and the cleaning time was 6 min. The reaction time at room temperature in the dark was 16 h. The drying temperature was 65 °C, the drying method was vacuum drying, and the drying time was 9 h.
[0079] S3. Buffer layer construction: The polydopamine-modified glass cellulose support substrate is immersed in the amphoteric buffer reaction solution and co-deposition grafting reaction is carried out at room temperature in the dark. After removal, the substrate is rinsed with deionized water to remove free components and dried to form an immobilized zwitterionic buffer interface layer on the modified surface of the substrate.
[0080] The amphoteric buffer reaction solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, and the solutes are aminopropyl sulfonate betaine and dopamine hydrochloride. The concentration of aminopropyl sulfonate betaine is 6 mg / mL, and the concentration of dopamine hydrochloride is 1.0 mg / mL. The co-deposition grafting reaction time is 7 h. The drying temperature is 50 °C, the drying method is vacuum drying, and the drying time is 12 h. This composite buffer layer can stabilize the local reaction environment in wastewater with large pH fluctuations, ensuring the stability of the detection signal.
[0081] S4. Preparation of coating solution: Disperse the dual-ligand co-coordinated Eu@MOF powder in deionized water and ultrasonically disperse to form a uniform suspension. Add branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent to the suspension in sequence, and continue ultrasonic dispersion to obtain the functional composite sensing coating solution.
[0082] The final concentration of the dual-ligand co-coordinated Eu@MOF powder in the suspension was 1.8 mg / mL, the final concentration of branched polyethyleneimine was 0.10 mg / mL, and the amount of quaternized polyethyleneimine added accounted for 15% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the amount of polyethylene glycol added was 8% of the total mass of the coating solution; the crosslinking agent was ethylene glycol diglycidyl ether, and the amount added accounted for 5% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine; the initial ultrasonic dispersion power was 280 W and the duration was 18 min, and the ultrasonic dispersion time after feeding was continued for 12 min. During the dispersion process, magnetic stirring at 350 r / min was used to ensure the uniformity of the system.
[0083] S5. Curing and molding: The functional composite sensing coating liquid is uniformly coated onto the substrate surface with the immobilized zwitterionic buffer interface layer using a scraping method. After controlling the wet film thickness, it is placed in a constant temperature environment for curing. After cutting, Eu@MOF fluorescent test paper is obtained.
[0084] The wet film thickness was 65 μm, the curing temperature was 50℃, and the curing time was 3 h; the size of the cut test strip was 0.6 cm × 3.2 cm.
[0085] Comparative Example 1: The only difference between this comparative example and Example 1 is that the quaternized polyethyleneimine component is removed from the functional sensing layer, and the corresponding reduction in mass is made up by branched polyethyleneimine. That is, on a dry basis, the functional sensing layer consists of 1.5 parts of dual-ligand co-coordinated Eu@MOF powder, 0.095 parts of branched polyethyleneimine, and 0.08 parts of polyethylene glycol. All other raw materials, proportions, and preparation steps are completely consistent with Example 1.
[0086] Comparative Example 2: The only difference between this comparative example and Example 1 is that the crosslinking agent ethylene glycol diglycidyl ether is not added during the preparation of the coating solution in step S4. All other raw materials, proportions and preparation steps are completely consistent with Example 1.
[0087] Comparative Example 3: The only difference between this comparative example and Example 1 is that in the amphoteric buffer reaction solution of step S3, dopamine hydrochloride is not added, and only aminopropyl sulfonate betaine is used as the single solute. The other raw materials, ratios and all preparation steps are completely consistent with Example 1.
[0088] Comparative Example 4: The only difference between this comparative example and Example 1 is that in step S1, the reaction product is directly vacuum dried after centrifugation and anhydrous ethanol solvent exchange, without isothermal coordination repair treatment. The other raw materials, ratios and all preparation steps are completely consistent with Example 1.
[0089] Comparative Example 5: The only difference between this comparative example and Example 1 is that the two steps of substrate modification in step S2 and buffer layer construction in step S3 are omitted, and branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent are not added in step S4; the unmodified glass cellulose membrane is directly immersed in a 1.5 mg / mL dual-ligand co-coordinated Eu@MOF powder suspension, and after immersion for 5 min, it is taken out and dried at 45°C for 2.5 h, and then cut into test paper of the same size. All other raw material parameters are completely consistent with those of Example 1.
[0090] I. Phosphate fluorescence detection performance test: Prepare phosphate standard solution and calibrate concentration according to HJ1092-2020 "Determination of total phosphorus in water by flow injection-ammonium molybdate spectrophotometric method". The excitation wavelength of the fluorescence spectrophotometer was set to 395 nm, and the emission wavelength scanning range was 550 nm to 700 nm. Test strips of the same specifications from Examples 1 to 3 and Comparative Examples 1 to 5 were taken and inserted into a 10 μmol / L phosphate standard solution, ensuring that the sensing area of the test strip was completely submerged below the liquid surface. The fluorescence intensity of the test strip at a wavelength of 615 nm was recorded as a function of time. The time when the fluorescence intensity dropped to 90% of the initial intensity was recorded as the response time. After the signal stabilized, the equilibrium fluorescence intensity was recorded. Six gradient concentrations of phosphate standard solutions (0.1 μmol / L, 0.5 μmol / L, 1 μmol / L, 5 μmol / L, 10 μmol / L, and 50 μmol / L) were prepared and the above test was repeated. A standard working curve of fluorescence intensity versus phosphate concentration was plotted. The phosphate detection limit of each test strip was calculated based on the concentration corresponding to a signal-to-noise ratio of three. Each group of samples was tested in parallel for 6 times, and the average value was taken as the final test result.
[0091] II. Wide pH Water Interference Resistance Test: The pH value of the test water sample was adjusted according to GB / T6920-1986 "Determination of pH Value of Water - Glass Electrode Method". A 10 μmol / L phosphate standard solution was prepared, and the pH value of the water sample was adjusted to six gradients: 4.0, 5.0, 6.0, 7.0, 8.0, and 9.0, respectively, using 0.1 mol / L hydrochloric acid solution and 0.1 mol / L sodium hydroxide solution. No additional liquid buffer reagent was added during the test. Test strips of the same specifications from Examples 1 to 3 and Comparative Examples 1 to 5 were immersed in phosphate water samples with different pH values. After the response reached equilibrium, the fluorescence intensity of each test strip at a wavelength of 615 nm was measured. The fluorescence intensity under pH 7.0 was used as the benchmark, and the relative deviation of fluorescence intensity under different pH conditions was calculated to evaluate the pH interference resistance of each test strip in the in-situ detection scenario without pretreatment. Each group of samples was tested in parallel three times at each pH gradient, and the average value was taken as the final test result.
[0092] III. Continuous Immersion Stability Test in Water: The immersion test procedure was performed according to GB / T1733-2020 "Determination of Water Resistance of Paints and Varnishes". Test strips of the same specifications from Examples 1 to 3 and Comparative Examples 1 to 5 were taken and completely immersed in neutral deionized water at pH 7.0. The strips were continuously immersed in a dark environment at room temperature, with fresh deionized water replaced every 12 hours to simulate a flowing water environment. The test strips were removed at 1h, 6h, 12h, 24h, and 72h of immersion. Excess surface moisture was gently absorbed with qualitative filter paper. The initial fluorescence intensity at 615nm and the response fluorescence intensity to 10μmol / L phosphate were measured. Using the corresponding values of unimmersed fresh test strips as a benchmark, the initial fluorescence retention rate and response sensitivity retention rate at different immersion times were calculated to evaluate the stability of each test strip under long-term in-situ immersion conditions. Each group of samples was tested in parallel three times at each time point, and the average value was taken as the final test result.
[0093] Table 1: Results of Phosphate Fluorescence Detection Performance Test
[0094] sample Response time / s <![CDATA[Detection limit / μmol·L⁻ 1 > Linear correlation coefficient R 2 ]] Example 1 28 0.032 0.9992 Example 2 31 0.031 0.9987 Example 3 32 0.043 0.9989 Comparative Example 1 62 0.187 0.9976 Comparative Example 2 35 0.038 0.9988 Comparative Example 3 33 0.035 0.9990 Comparative Example 4 36 0.047 0.9981 Comparative Example 5 78 0.264 0.9953
[0095] Note: This test was conducted according to HJ1092-2020 "Determination of Total Phosphorus in Water - Flow Injection-Ammonium Molybdate Spectrophotometric Method". The phosphate standard solution was prepared and its concentration was calibrated. The excitation wavelength was 395 nm, and the emission wavelength was 615 nm. The response time was defined as the time it took for the fluorescence intensity to drop to 90% of the initial intensity. The detection limit was calculated based on three times the signal-to-noise ratio. The linear detection range was 0.1 μmol / L to 50 μmol / L. All data are the average of 6 parallel tests.
[0096] Table 2: Test Results of Anti-interference Performance in Wide pH Water Bodies
[0097] sample Relative deviation of fluorescence intensity at pH 4.0 / % Relative deviation of fluorescence intensity at pH 9.0 / % Example 1 3.2 2.8 Example 2 5.7 4.9 Example 3 4.1 3.6 Comparative Example 1 3.5 3.0 Comparative Example 2 3.3 2.9 Comparative Example 3 21.5 18.3 Comparative Example 4 3.4 2.9 Comparative Example 5 35.7 30.2
[0098] Note: This test was conducted according to GB / T6920-1986 "Determination of pH in Water - Glass Electrode Method" to adjust the pH of the water sample. The phosphate concentration in the test system was 10 μmol / L, and no additional liquid buffer reagent was added during the test. The relative deviation was calculated based on the equilibrium fluorescence intensity under pH 7.0 conditions. The smaller the absolute value of the deviation, the stronger the test paper's resistance to pH interference. All data are the average of three parallel tests.
[0099] Table 3: Performance retention rate test results after continuous immersion in water for 72 hours
[0100] sample Initial fluorescence retention rate / % Response sensitivity retention rate / % Example 1 92.4 89.7 Example 2 87.1 83.5 Example 3 89.6 86.2 Comparative Example 1 90.1 87.3 Comparative Example 2 61.3 52.8 Comparative Example 3 54.7 48.1 Comparative Example 4 65.2 59.4 Comparative Example 5 28.5 21.3
[0101] Note: This test follows the immersion procedure of GB / T1733-2020 "Determination of water resistance of paints and varnishes". The immersion medium is neutral deionized water with pH 7.0. Fresh medium is replaced every 12 hours to simulate a flowing water environment. The retention rate is calculated based on the performance value of fresh test paper that has not been soaked. The higher the retention rate, the better the long-term immersion stability of the test paper. All data are the average of three parallel tests.
[0102] Based on Examples 1-3 and Comparative Example 1, and in conjunction with Table 1, it can be seen that the introduction of quaternized polyethyleneimine into the sensing layer can effectively improve the detection response speed and sensitivity of phosphate. The positive charge carried by this component can actively enrich phosphate anions in the water through electrostatic interaction, shorten the ion mass transfer path and increase the concentration of the target substance at the interface. The addition or subtraction of this component has no significant effect on the test paper's resistance to pH interference and long-term immersion stability.
[0103] As can be seen from Examples 1-3 and Comparative Example 2, and Table 3, the introduction of crosslinking agent is the key to improving the water immersion stability of the sensing layer. Ethylene glycol diglycidyl ether can undergo a ring-opening reaction with polyethyleneimine to form a three-dimensional covalent crosslinked network, which firmly embeds MOF particles inside the network, preventing material detachment and loss under long-term immersion. Whether or not the crosslinking is performed has no significant impact on the initial detection performance of the test strip.
[0104] Based on Examples 1-3 and Comparative Example 3, and in conjunction with Tables 2 and 3, it can be seen that constructing a buffer layer by co-deposition of aminopropyl sulfonate betaine and polydopamine can simultaneously improve the interfacial buffering capacity and the fixation strength of the buffer agent. The three-dimensional polydopamine network can not only anchor the amphoteric buffer components through covalent bonds, but also help maintain the stability of the local microenvironment, so that the test strip can still maintain a stable detection signal in water bodies with wide pH fluctuations, and the buffer components are not easily lost under long-term immersion.
[0105] Based on Examples 1-3 and Comparative Example 4, and in conjunction with Tables 1 and 3, it can be seen that the isothermal coordination repair treatment after solvothermal treatment can effectively improve the aqueous phase stability of MOF powder. This treatment can repair the coordination unsaturated sites on the crystal surface, reduce the number of hydrolytic active sites, and make the test paper less prone to skeleton collapse and fluorescence baseline drift during long-term immersion in water. At the same time, it also has a certain optimization effect on the initial detection performance.
[0106] As can be seen from Examples 1-3 and Comparative Example 5, and Tables 1, 2 and 3, the multi-layer integrated design of this application has comprehensive performance advantages over test strips prepared by conventional impregnation methods. The substrate modification, buffer layer construction and functionalized sensing layer work together to achieve rapid and sensitive detection, wide pH interference resistance and long-term immersion stability, which can better adapt to the application scenario of in-situ immersion detection in natural water bodies.
[0107] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water, characterized in that: From bottom to top, it includes a polydopamine-modified glass cellulose support substrate, a supported zwitterionic buffer interface layer, and a functional sensing layer; the supported zwitterionic buffer interface layer is covalently grafted onto the modified surface of the polydopamine-modified glass cellulose support substrate, and the functional sensing layer is cross-linked and supported on the surface of the supported zwitterionic buffer interface layer. Based on dry weight, the functional sensing layer is composed of the following components: 1.2 to 1.8 parts of dual-ligand co-coordinated Eu@MOF powder, 0.06 to 0.10 parts of branched polyethyleneimine, 0.01 to 0.02 parts of quaternized polyethyleneimine, and 0.06 to 0.10 parts of polyethylene glycol.
2. The Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 1, characterized in that: The dual-ligand co-coordinated Eu@MOF powder is a single-framework co-coordinated crystal phase, prepared by a solvothermal reaction of europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate, with a molar ratio of 1:(0.8-1.2):(0.15-0.3):(2.0-3.0).
3. The Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 1, characterized in that: The immobilized zwitterionic buffer interface layer is a composite thin layer formed by co-deposition of aminopropyl sulfonate betaine and polydopamine, with a thickness of 10-20 μm.
4. The Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 1, characterized in that: The thickness of the polydopamine-modified glass cellulose support substrate is 0.2–0.3 mm.
5. A method for preparing Eu@MOF fluorescent test strips for rapid in-situ detection of phosphate in environmental water, characterized in that, The preparation of the Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to any one of claims 1 to 4 comprises the following steps: S1. Powder preparation: Weigh europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid, 2-aminoterephthalic acid and sodium acetate trihydrate according to the preset molar ratio, add them to the mixed solvent and ultrasonically disperse them, transfer them to a hydrothermal reactor for solvothermal reaction, and after natural cooling, centrifuge, wash and vacuum dry them in sequence to obtain dual-ligand co-coordinated Eu@MOF powder; S2. Substrate modification: The glass cellulose membrane substrate is immersed in anhydrous ethanol and ultrasonically cleaned. After being taken out and dried, it is immersed in polydopamine modification solution and reacted at room temperature in the dark. After being taken out, it is rinsed with deionized water until the washing solution is colorless. After drying, polydopamine modified glass cellulose support substrate is obtained. S3. Buffer layer construction: The polydopamine-modified glass cellulose support substrate was immersed in the amphoteric buffer reaction solution and co-deposition grafting reaction was carried out at room temperature in the dark. After removal, the substrate was rinsed with deionized water to remove free components and dried to form an immobilized zwitterionic buffer interface layer on the modified surface of the substrate. S4. Preparation of coating solution: Disperse the dual-ligand co-coordinated Eu@MOF powder in deionized water and ultrasonically disperse to form a uniform suspension. Add branched polyethyleneimine, quaternized polyethyleneimine, polyethylene glycol and crosslinking agent to the suspension in sequence, and continue ultrasonic dispersion to obtain the functional composite sensing coating solution. S5. Curing and molding: The functional composite sensing coating liquid is uniformly coated onto the substrate surface with the immobilized zwitterionic buffer interface layer using a scraping method. After controlling the wet film thickness, it is placed in a constant temperature environment for curing. After cutting, Eu@MOF fluorescent test paper is obtained.
6. The method for preparing Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 5, characterized in that: In step S1, the mixed solvent is composed of N,N-dimethylformamide, anhydrous ethanol and deionized water in a volume ratio of 6:(1.8-2.2):(1.8-2.2). The temperature of the solvothermal reaction is 115-125℃ and the reaction time is 7-9h. After centrifugation, the reaction product is subjected to solvent exchange with anhydrous ethanol 2-3 times, isothermal coordination repair treatment at 60-80℃ for 12-16h, and then vacuum drying.
7. The method for preparing Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 5, characterized in that: In step S2, the polydopamine modification solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0 to 9.0, the solute in the polydopamine modification solution is dopamine hydrochloride, and the solute concentration is 1.5 to 2.5 mg / mL; the drying temperature is 55 to 65°C, and the drying method is vacuum drying.
8. The method for preparing Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 5, characterized in that: In step S3, the amphoteric buffer reaction solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH of 7.5–8.5, and the solutes are aminopropyl sulfonate betaine and dopamine hydrochloride; wherein the concentration of aminopropyl sulfonate betaine is 4–6 mg / mL and the concentration of dopamine hydrochloride is 0.5–1.0 mg / mL; the drying temperature is 40–50°C, and the drying method is vacuum drying.
9. The method for preparing Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 5, characterized in that: In step S4, the final concentration of the dual-ligand co-coordinated Eu@MOF powder in the suspension is 1.2–1.8 mg / mL, the final concentration of the branched polyethyleneimine is 0.06–0.10 mg / mL, the amount of quaternized polyethyleneimine added is 10–15% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine, the amount of polyethylene glycol added is 5–8% of the total mass of the coating solution, and the crosslinking agent is ethylene glycol diglycidyl ether, the amount added is 2–5% of the total mass of branched polyethyleneimine and quaternized polyethyleneimine.
10. The method for preparing Eu@MOF fluorescent test strip for in-situ rapid detection of phosphate in environmental water bodies according to claim 5, characterized in that: In step S5, the wet film thickness is 55-65 μm, the curing temperature is 40-50°C, and the curing time is 2-3 h.
